2014
DOI: 10.1074/jbc.m114.569244
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Nucleolar Histone Chaperone NPM1 Triggers Rearrangement of Heterochromatin and Synergizes with a Deficiency in DNA Methyltransferase DNMT3A to Drive Ribosomal DNA Transcription

Abstract: Background: NPM1 is a nucleolar histone chaperone mutated in cancer. Results: NPM1-deficient cells display rearrangement of perinucleolar heterochromatin, and simultaneous knockdown of NPM1 and DNMT3A enhances transcription of ribosomal DNA. Conclusion: NPM1 loss disrupts heterochromatin organization around the nucleolus. Significance: Rearrangement of heterochromatin in NPM1-deficient cells may be of importance in tumor development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 83 publications
3
58
0
Order By: Relevance
“…In somatic cells, NPM1 − one of the NPM2 homologs − undergoes phase separation in a concentration-dependent manner together with the arginine-rich proteins and rRNAs that are required for ribosome biogenesis. This event is critical for structural organization of the somatic nucleoli and, presumably, required to control the activity of ribosome biogenesis (Feric et al, 2016;Holmberg Olausson et al, 2014;Mitrea et al, 2016). In our study, we found that NPM2 has the ability to form a spherical body together with other proteins and RNAs in a concentration-dependent manner.…”
Section: (N>3 Each) (B) Npm2 Protein Expression Levels Inmentioning
confidence: 48%
“…In somatic cells, NPM1 − one of the NPM2 homologs − undergoes phase separation in a concentration-dependent manner together with the arginine-rich proteins and rRNAs that are required for ribosome biogenesis. This event is critical for structural organization of the somatic nucleoli and, presumably, required to control the activity of ribosome biogenesis (Feric et al, 2016;Holmberg Olausson et al, 2014;Mitrea et al, 2016). In our study, we found that NPM2 has the ability to form a spherical body together with other proteins and RNAs in a concentration-dependent manner.…”
Section: (N>3 Each) (B) Npm2 Protein Expression Levels Inmentioning
confidence: 48%
“…In human colon carcinoma cells lacking DNMT1 or DNMT3B, the levels of the 47S primary rRNA transcript are significantly increased (181). In glioblastoma cells deficient in NPM1, a nucleolar histone chaperone, loss of DNMT3 also synergistically enhances rDNA transcription (180). Indeed, low levels of DNA methylation at rDNA genes are found in many African American women with endometrial carcinoma (178).…”
Section: Disease Progressionmentioning
confidence: 96%
“…rDNA hypomethylation is found in a wide range of cancers, such as hepatocellular carcinoma, endo-metrial cancer, brain cancer, and colon cancer (178)(179)(180)(181). Human hepatocellular carcinoma cells display DNA hypomethylation at rDNA promoters that coincides with the reactivation of silenced rDNA expression (181).…”
Section: Disease Progressionmentioning
confidence: 99%
“…Integration of NPM1 into the nucleolus is dependent on its multivalent interactions with RNA and proteins containing arginine-rich linear motifs (Mitrea et al, 2016). Furthermore, loss of NPM1 triggers rearrangement of perinucleolar heterochromatin (Holmberg Olausson et al, 2014;Murano et al, 2008), suggesting direct interactions between NPM1 and heterochromatin.…”
Section: Cutandrunrnase Probes the Requirement Of Architectural Rna Inmentioning
confidence: 99%